Correlations and Entanglement of Microwave Photons Emitted in a Cascade Decay - Gasparinetti, Simone; Pechal, Marek; Besse, Jean-Claude; Mondal, Mintu; Eichler, Christopher; Wallraff, Andreas (Physical Review Letters, 2017)
We use a three-level artificial atom in the ladder configuration as a source of correlated, single microwave photons of different frequency. The artificial atom, a transmon-type superconducting circuit, is driven at the two-photon transition between ground and second-excited state, and embedded into an on-chip switch that selectively routes different-frequency photons into different spatial modes. Under continuous driving, we measure power cross-correlations between the two modes and observe a crossover between strong antibunching and superbunching, typical of cascade decay, and an oscillatory pattern as the drive strength becomes comparable to the radiative decay rate. By preparing the source in a superposition state using an excitation pulse, we achieve deterministic generation of entangled photon pairs, as demonstrated by nonvanishing phase correlations and more generally by joint quantum state tomography of the two itinerant photonic modes.
CRIS-Team Scopus Importer:2022-06-27